Factors Affecting The Migration Of 222Rn In Subsurface Environments: The Dependence Of Emanation Coefficient On Ore Properties - Stephen R. Pogorski; Nicholas Busigin; Colin R. Phillips (Society for Mining, Metallurgy & Exploration, 1981)
The movement of radon away from its source in porous media is determined by two key parameters: the fraction of the total radon formed which enters the intergranular pore spaces, termed the emanation coefficient, and the transport processes which exist in these pores such as diffusion and convection. The first parameter, the emanation coefficient, is of primary importance since it is a measure of the actual amount of radon which is free to migrate within the media. The effects of particle size and radium concentration on the emanation coefficient were examined using a quartz-pebble conglomerate ore from the Elliot Lake mining district of Ontario. It was found that the smallest particle size examined (<74 µm) had the highest radium concentration and contributed the most to the radon emanation. A one-to-one correspondence between radium concentrations for the various particle size fractions and radon emanation was not observed. Samples were examined using scanning electron microscopy and very small particulates were observed to be present on the particle surfaces. When these very small particulates were removed from the host particle surfaces by rinsing, the radon emanation decreased by a factor of 17. This result indicates that most of the emanation comes from the very small particles. The effect of moisture on the emanation coefficient was examined qualitatively and a trend of increased radon release with moisture content was noted.